2016
DOI: 10.1007/s00595-016-1413-6
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative complications after middle lobe-preserving surgery for secondary lung cancer

Abstract: While postoperative complications after middle lobe-preserving surgery are manageable, their high incidence should be considered when performing this surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Compromised pulmonary functions by previous surgery, technical surgical difficulties related to redo surgeries, higher rate of postoperative complications, and alternative curative options certainly represent a main issue when faced with a patient with recurrent or metachronous lung cancer. 1 , 2 , 3 However, redo surgery, if the patient is resectable and can tolerate surgery, still represent the standard of care. 1 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compromised pulmonary functions by previous surgery, technical surgical difficulties related to redo surgeries, higher rate of postoperative complications, and alternative curative options certainly represent a main issue when faced with a patient with recurrent or metachronous lung cancer. 1 , 2 , 3 However, redo surgery, if the patient is resectable and can tolerate surgery, still represent the standard of care. 1 …”
Section: Discussionmentioning
confidence: 99%
“…However, some case reports demonstrated that in selected cases, ML might preserve a great amount of lung function, reducing surgery risk and improving postoperative quality of life. 2 , 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common post-operative complications in the surgical treatment of patients with non-small-cell lung cancer is represented by air leaks [ 33 , 34 , 35 ]. Although no significant differences were reported in this study among the three periods, associations were detected between the presence of these complications and both the more advanced T stage ( p = 0.018) and the more advanced cancer stage ( p = 0.022).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, right lower middle lobe-preserving lobectomy contributes to postoperative lung function. Although reports of middle lobe preservation have been published [2][3][4], it may produce torsion. Emphysematous changes in the residual middle lobe may result from volume mismatch with the thoracic cavity during followup [2].…”
Section: Commentmentioning
confidence: 99%